Stage two development of new venture creation : using a food and shopping guide as a promotional tool for Holland Village. - Chew, Han Ping. (2008)
This report details the development of the entrepreneurial process of coming up with a Food and Shopping Guide for Holland Village. A team of four members was formed in July 2003 to work on increasing the awareness of Holland Village. The four options of promoting Holland Village were analyzed and a consensus was reached to publish a Holland Village Food and Shopping Guide.